2012
DOI: 10.1038/hr.2012.133
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol consumption and cardiovascular disease incidence in men with and without hypertension: the Suita study

Abstract: The relationship between alcohol consumption and the risk for cardiovascular disease (CVD) is U-shaped, whereas alcohol drinking is linearly associated with blood pressure, and the CVD risk also increases linearly according to blood pressure level. Accordingly, we investigated the net effect of alcohol consumption and hypertension on CVD and its subtypes in this study. A 13-year prospective study of 2336 Japanese men who were free from CVD was performed; ex-drinkers were excluded. The participants were divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
1
24
0
2
Order By: Relevance
“…Among the hypertensive individuals, the risk for total and ischemic stroke was the highest in heavy drinkers, whereas in nonhypertensive individuals, there was no significant increase or decrease in the hazard ratios for stroke and its subtypes in drinkers. The results of the study by Higashiyama et al [24] were similar to ours in the present study. In the study by Kiyohara et al [25], the risk for cerebral haemorrhage among hypertensive individuals (!160/95 mmHg) was significantly increased in heavy drinkers compared with nondrinkers; the relationship between alcohol consumption and the risk for cerebral infarction was U-shaped; also, an increase in the risk for haemorrhagic and cerebral stroke was not shown in any drinkers among the nonhypertensive individuals (<160/95 mmHg).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Among the hypertensive individuals, the risk for total and ischemic stroke was the highest in heavy drinkers, whereas in nonhypertensive individuals, there was no significant increase or decrease in the hazard ratios for stroke and its subtypes in drinkers. The results of the study by Higashiyama et al [24] were similar to ours in the present study. In the study by Kiyohara et al [25], the risk for cerebral haemorrhage among hypertensive individuals (!160/95 mmHg) was significantly increased in heavy drinkers compared with nondrinkers; the relationship between alcohol consumption and the risk for cerebral infarction was U-shaped; also, an increase in the risk for haemorrhagic and cerebral stroke was not shown in any drinkers among the nonhypertensive individuals (<160/95 mmHg).…”
Section: Discussionsupporting
confidence: 93%
“…In INTERSALT study, significant relation of heavy drinking (three to four or more drinks/day) to hypertension was observed in both men and women [23]. However, few studies [24,25] investigated the cumulative effects of hypertension and alcohol drinking on stroke in a prospective study of the general population. Recently, Higashiyama et al [24] reported a 13-year prospective study among 2336 Japanese men who were free from CVD at baseline.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Of the 21 studies, 18 received 6 scores or higher on the Newcastle-Ottawa quality assessment scale and were considered to be of high methodological quality. [11][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27][28][29] …”
Section: Quality Assessmentmentioning
confidence: 99%
“…Porém quando utilizada em excesso o risco torna-se aumentado 272 , sendo assim um fator protetor para dislipidemias quando usado corretamente.…”
Section: Discussão 193unclassified